Powerful sand photocatalyst for solar photo-Fenton degradation of antibiotics in wastewater treatment plant effluent - Lima, Karla V.L. [UNESP]; de Jesus, Jany H.F. [UNESP]; Nogueira, Raquel F.P. [UNESP] (Elsevier, 2025)
A catalyst based on iron oxide supported on sand (IOSS) was applied in the solar photo-Fenton process for the degradation of the antibiotics sulfamethoxazole (SMX) and trimethoprim (TMP) in Wastewater Treatment Plant (WWTP) effluent. The characterization by X-ray Diffraction, Scanning Electron Microscopy, and X-ray Photoelectron Spectroscopy confirmed the presence of hematite on the sand surface. The catalyst effectively degraded both antibiotics, achieving complete degradation (concentration below the limit of detection) after 180 min, using a 0.5 g L−1 catalyst, 10 mmol L−1 H2O2 at pH 3.0. Additionally, the IOSS maintained its efficiency at higher pH levels (5.0 and 7.0) in ultrapure water, achieving degradation percentages above 90 % for SMX and TMP at pH 7. The catalyst demonstrated stability over five reuse cycles. Furthermore, the material showed high performance in WWTP effluent, achieving degradation above 90 % for SMX and 100 % for TMP in this matrix at pH 3, and under solar irradiation exposure, highlighting its viability under natural irradiation for treatment of WWTP effluents.